2007
DOI: 10.1007/s10936-007-9064-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Phonological Similarity Within and Across Languages

Abstract: The influence of phonological similarity on bilingual language processing was examined within and across languages in three experiments. Phonological similarity was manipulated within a language by varying neighborhood density, and across languages by varying extent of cross-linguistic overlap between native and non-native languages. In Experiment 1, speed and accuracy of bilinguals' picture naming were susceptible to phonological neighborhood density in both the first and the second language. In Experiment 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 63 publications
4
51
0
Order By: Relevance
“…The observed reaction time (RT) values were within the range reported for picture description tasks (Smith and Wheeldon 1999; Allum and Wheeldon 2007; Marian et al 2008). As in our previous study, the Chinese speakers showed significantly shorter RT values (on average, saving over 170 ms or nearly 20% of RT), but no significant scaling of RT with ln( ID ) was observed.…”
Section: Discussionsupporting
confidence: 70%
“…The observed reaction time (RT) values were within the range reported for picture description tasks (Smith and Wheeldon 1999; Allum and Wheeldon 2007; Marian et al 2008). As in our previous study, the Chinese speakers showed significantly shorter RT values (on average, saving over 170 ms or nearly 20% of RT), but no significant scaling of RT with ln( ID ) was observed.…”
Section: Discussionsupporting
confidence: 70%
“…The speech evaluators, however, tended to not be NSs of Spanish, but rather were NSs of English with varying levels of familiarity with Spanish-accented speech. So the pronunciation and accent evaluations in Arizona may have resulted in reducing the number of teachers in the classroom who shared an L1 with the students, something that has been shown to be beneficial in language learning programmes (Hertel & Sunderman, 2009;Marian et al, 2008;Park, 2012). As in Scales et al's (2006) and Isaacs' (2008) research, we found that comprehension was a high priority for students in accepting a speaker as a teacher.…”
supporting
confidence: 51%
“…For bilingual listeners, auditory input in one language activates possible word candidates regardless of language membership (e.g., Marian & Spivey, 2003a, 2003b). This input-driven language co-activation is observed across different proficiency levels, ages of onset of language acquisition, and highly diverse language pairs (e.g., Blumenfeld & Marian, 2007, 2013; Canseco-Gonzalez et al, 2010; Cutler, Weber, & Otake, 2006; Ju & Luce, 2004; Marian, Blumenfeld, & Boukrina, 2008; Weber & Cutler, 2004). Resolving such cross-linguistic competition has been posited to require cognitive inhibition skills (e.g., Green, 1998; Shook & Marian, 2013).…”
Section: Introductionmentioning
confidence: 97%